Analysis of methods of managing the environmental safety of the navigation passage of ships of maritime transport - Sagin, Sergii V.; Sagin, Sergii S.; Madey, Volodymyr (Technology audit and production reserves, 2023)
The requirements of the MARPOL international convention on ensuring the environmental performance of marine diesel engines in relation to the emission of sulfur oxides, as well as marine fuels during navigation passages of sea transport vessels in special ecological areas, are given. The use of scrubber cleaning of exhaust gases and the use of fuel mixtures, which include biodiesel fuel, are considered as methods that meet these requirements. The research was carried out on ships of the Bulker Carrier class with deadweight of 63,246 tons during the navigation transition between the ports of Northern Europe. One of the vessels used scrubber cleaning of exhaust gases as a method of environmental safety management. The other is the use of fuel mixtures, which include biodiesel fuel. Both vessels are equipped with a 5S60ME-C8.2 MAN-Diesel&Turbo marine diesel engine as the main engine, and three 6EY18ALW Yanmar diesel engines as auxiliary engines. The ratio of sulfur oxides to carbon oxides – SO2/CO2 – was chosen as an indicator for evaluating the effectiveness of environmental safety management methods. This value was monitored and regulated by an automatic monitoring system. It was found that both methods meet the requirements of the MARPOL convention, namely, they will support the SO2/CO2 ratio in the range of 2.29–4.17 (when in special environmental control zones) and in the range of 6.46–20.83 (when in outside the zone of special environmental control). The use of environmental safety management methods increases energy costs for ensuring this process. When using exhaust gas scrubbing, additional power losses reach 237–278 kW. In the case of using a fuel mixture that includes biodiesel fuel, power losses amount to 18–20 kW. It has been experimentally confirmed that the use of a fuel mixture that includes biodiesel fuel is characterized by a lower level of environmental sustainability. At the same time, compared to the use of scrubber cleaning of exhaust gases, this method requires less energy consumption and is also characterized by simpler additional equipment. In this regard (and also taking into account that all the requirements of Annex VI MARPOL are provided), it is recommended as the main one to ensure the environmental safety of navigation passages of sea transport vessels.